Foucault, freedom and sovereignty - Prozorov, Sergei (Ashgate Pub., 2007)
Against the prevailing interpretations which disqualify a Foucauldian approach from the discourse of freedom, this study offers a novel concept of political freedom and posits freedom as the primary axiological motif of Foucault's writing.